2023
DOI: 10.1039/d2cp04397a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral molecule induced valley polarization enhancement of MoS2

Abstract: Monolayers of transition metal dichalcogenides (TMDCs) are atomically thin direct-bandgap semiconductors with potential applications in nanoelectronics, opto-electronics, and electrochemical sensing. Recent theoretical and experimental results have suggested that they are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Even linear polarization impingent on the nanostructures transduces a valley polarization difference in MoS 2 . Similary, enhanced valley contrast was reported by depositing chiral molecules directly on MoS 2 . Other recent advances suggest that some of the polarization selectivity of charge transfer upon photoexcitation is instrinsic to the chiral nature of the molecules used in the perovskite structure, and not necessarily created by the light source .…”
Section: Outlook and Opportunitiessupporting
confidence: 59%
See 1 more Smart Citation
“…Even linear polarization impingent on the nanostructures transduces a valley polarization difference in MoS 2 . Similary, enhanced valley contrast was reported by depositing chiral molecules directly on MoS 2 . Other recent advances suggest that some of the polarization selectivity of charge transfer upon photoexcitation is instrinsic to the chiral nature of the molecules used in the perovskite structure, and not necessarily created by the light source .…”
Section: Outlook and Opportunitiessupporting
confidence: 59%
“…Similary, enhanced valley contrast was reported by depositing chiral molecules directly on MoS 2 . 136 Other recent advances suggest that some of the polarization selectivity of charge transfer upon photoexcitation is instrinsic to the chiral nature of the molecules used in the perovskite structure, and not necessarily created by the light source. 137 Although this general phenomenon of chirality induced spin selectivity (CISS) has promise in fields adjacent to the subject of this review, 138 for purposes of fast optical modulation of spin behavior and associated magnetism the relatively fixed nature of chiral sense makes these architectures less relevant.…”
Section: Outlook and Opportunitiesmentioning
confidence: 99%
“…Research on single monolayer MoS 2 and WSe 2 interfaced with chiral perovskites showed changes in the degree of valley polarization and the effect was attributed to the spin-selective charge injection from the chiral perovskite, i.e., CISS . A similar enhancement in valley polarization was also observed when d -histidine was interfaced with a monolayer of MoS 2 . Here, the spin-dependent charge redistribution properties of the histidine, and strong hybridization between histidine and the MoS 2 , led to the degree of polarization at the + K valley being 7.73% and the − K valley being 1.6%.…”
Section: Materials and Molecules Exhibiting Cissmentioning
confidence: 55%
“…177 A similar enhancement in valley polarization was also observed when D-histidine was interfaced with a monolayer of MoS 2 . 186 Here, the spin-dependent charge redistribution properties of the histidine, and strong hybridization between histidine and the MoS 2 , led to the degree of polarization at the +K valley being 7.73% and the −K valley being 1.6%. Note that spin-dependent charge redistributions in chiral molecules can lead to spontaneous magnetization, 20 and application of external magnetic fields to TMDs can cause a Zeeman energy splitting that increases valley contrast.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 89%